1986
DOI: 10.3109/10408448609023767
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Food Poisoning: Toxicology and Clinical Aspects

Abstract: Histamine poisoning can result from the ingestion of food containing unusually high levels of histamine. Fish are most commonly involved in incidents of histamine poisoning, although cheese has also been implicated on occasion. The historic involvement of tuna and mackerel in histamine poisoning led to the longtime usage of the term, scombroid fish poisoning, to describe this food-borne illness. Histamine poisoning is characterized by a short incubation period, a short duration, and symptoms resembling those a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
367
0
32

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 624 publications
(399 citation statements)
references
References 188 publications
0
367
0
32
Order By: Relevance
“…The intoxication symptoms are usually mild including reddening on the face, neck and upper chest, vomiting, flushing, nausea and abdominal cramps. Putrescine and cadaverine could enhance the toxicity of histamine by inhibiting diamine oxidase involved in histamine metabolism (Taylor 1986). Whilst tyramine is reported to induce migraine, increase blood pressure and cause hypertension (Shalaby 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intoxication symptoms are usually mild including reddening on the face, neck and upper chest, vomiting, flushing, nausea and abdominal cramps. Putrescine and cadaverine could enhance the toxicity of histamine by inhibiting diamine oxidase involved in histamine metabolism (Taylor 1986). Whilst tyramine is reported to induce migraine, increase blood pressure and cause hypertension (Shalaby 1996).…”
Section: Introductionmentioning
confidence: 99%
“…During fish spoilage, bacterial decarboxylases catalyze the conversion of amino acids into biogenic amines. Scombroid poisoning incidents were frequently caused by the consumption of scombroid fish such as mackerel, bonito, tuna, and saury which are rich in histidine (Taylor 1986). However, the available literatures generate inconsistent results on the correlation between the formation of amines and their precursors, amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…However, if an excessive amount of biogenic amines is ingested or if the normal catabolic routes are inhibited or genetically deficient, several physiological disorders can occur (ten Brink et al, 1990). Histamine poisoning is sometimes referred to as "scombroid fish poisoning" due to illness resulting from consumption of fish such as tuna, mackerel and sardines; while high levels of tyramine in cheese causes a phenomenon known as the "cheese reaction" (Taylor, 1986;ten Brink et al, 1990). These false food allergies are of particular importance in wine, because the presence of ethanol, acetaldehyde and other biogenic amines may promote the harmful effects of histamine and tyramine by inhibiting their normal metabolism in humans (Landete et al, 2006).…”
Section: Yeast Speciesmentioning
confidence: 99%
“…It is also reported that histamine poisoning occurs more frequently in individuals with allergic inheritance (19,20). Our patients had no prior history of allergic diseases, their eosinophil counts were normal, and the IgE level of only case 4 was slightly high ( Table 1).…”
Section: Discussionmentioning
confidence: 95%